A Comparative Study between Matrix Converter Fed InductionMotor Drive and Dual-Matrix Converter Fed Open-End WindingInduction Motor Drive - Beladel, A.; Kouzou, A.; Hafaıfa, A.; Sunter, Sedat; Mahıa, D. (Fırat University, 2017)
This paper deals with a comparative study between the control of three to three phase matrix converter feeding astar-connected three phase induction machine and the control of three to three phase dual matrix converterfeeding an open-end winding induction machine. The control strategy used in both cases is based on a proposeddirect transfer function control approach of Venturini algorithm which allows to obtain a unity power factor atthe input side to boost the output phase voltage up to 150% compared to the input phase voltage, while keepingthe main advantage of the matrix converter by providing a fully bidirectional power flow operation. The mainobjective of using the open-end winding topology is to ensure the minimization of the common mode voltagewhich is clearly observed in the case of star-connected winding. Simulation results are presented under bothcontrol strategies, where both matrix converters are supplied from the same three-phase power source. Whereas;the two output voltage system of the dual matrix converter are shifted with 180 degrees. Based on the obtainedresults the performances of the both control approaches are technically discussed.